Derrida and his shadow - Ronell Avital (Filozofija i Društvo)
Rerouting the tradition of defiant putdown, his name is a shibboleth for troubled intervention, still unearthing values stubbornly uninterrogated by other branches of philosophical enquiry. He drew from Carl Schmitt the persistent atmospherics of hostility to politicize social aspects of aggregation and Mitsein. The oeuvre of Jacques Derrida thus continues to stir hostility, generating implications of seething mistrust for the textual and institutional strategies of a “Derridean” workspace. This is not the first time that philosophy has been exposed to bad faith or phobic taunts. Since Socrates’s countdown, we know, as Arendt alerts us, that philosophy continually faces state hostility. What provokes different types and gradations of philosophical hostility, prompting a perceptible level of anger-to this day, dispensing the calculated dosages of mistrust that issue from other philosophers and civic cohorts? Or is hostility-and the anger that it breeds, whether historically latent or effective, part and parcel of the philosophical profile-a course of action? Are philosophers, while rhetorically armed to the teeth, basically unarmed warriors, politically hungry, as in the differently deposed cases of Plato and Heidegger? It could certainly be the case that what attracts hostility is mainly a question of the objects that are brought into play. But there’s something more at stake.